An In-Depth Study of Traffic Congestion Detection and Management in Delhi - Choudhury, D. K.; Gupta, Siddharth (Prabandhan: Indian Journal of Management, 2015)
The traffic in Delhi is a very important issue as the city experiences acute traffic problems in different locations. The commuters lose unpredicted and unproductive time on the road because of traffic jams. Though the roads of Delhi, by and large, are pretty wide, but still, there are traffic jams on the roads, mainly because the number of vehicles on the roads are more than the traffic load bearing capacity of the roads. In Delhi, the traffic is managed by the Delhi Traffic Police. In 1978, the Delhi Traffic Police Act was enforced and came into being. It looks into all types of traffic problems and suggests the possible solutions to the government. The traffic management plan prepared and implemented by the Delhi Police is based on four principles: regulations, road safety education, engineering solutions, and enforcement strategies. It was observed that the main focus of the Delhi Traffic Police is on removing the congestions which are experienced in prime locations to ease the flow of traffic. The objectives of this research work were to study the present traffic congestion problem in different main roads of Delhi, and to offer possible solutions to resolve the issue of traffic congestion, and also to find out the different safety measures undertaken by the Delhi Traffic Police to ensure the safe flow of traffic in Delhi.